Do Political Connections Affect Tax Avoidance in Indonesia? A Systematic Review and Meta-Analysis - Nafis Dwi Kartiko; Amrie Firmansyah (Educoretax, 2023)
Previous correlational studies have shown a significant effect between political connections and tax avoidance. However, this also cannot deny other empirical facts which state that there is no significant influence between political connections and tax avoidance. This study aims to generalize the results of previous studies that discuss the influence of political connections and tax avoidance in Indonesia. Quantitative methods were chosen to analyze this; the researchers used Systematic Review and Meta-Analysis. We searched for eligible studies from the databases Garba Rujukan Digital (GARUDA), Ebsco, and Google Scholar until 17 September 2022. Meta-analysis was carried out using STATA software with the help of Microsoft Excel to calculate the effect size of each study data. Fourteen studies were successfully netted for analysis, of which 14 developed into 29 data using the data available in each study. We find that the relationship between political connections and tax avoidance in Indonesia has an insignificant direction; this is indicated by the value of z = -1.23 and p-value of 0.22 or above 0.05. It is the latest study in Indonesia to investigate the relationship between political connections and tax avoidance. Furthermore, the test results indicate that differences in tax avoidance proxies affect the test results for political connections. In contrast, there was no significant effect on the political connection proxy. The relevant tax authorities can consider significant tax avoidance proxies for political connections as one of the detection indicators in the Compliance Risk Management of Taxpayer Supervision.